Differential genomic imprinting and expression of imprinted microRNAs in testes-derived male germ-line stem cells in mouse. - Ji Young Shin (PLoS ONE, 2011)
BACKGROUND: Testis-derived male germ-line stem (GS) cells, the in vitro counterpart of spermatogonial stem cells (SSC), can acquire multipotency under appropriate culture conditions to become multipotent adult germ-line stem (maGS) cells, which upon testicular transplantation, produce teratoma instead of initiating spermatogenesis. Consequently, a molecular marker that can distinguish GS cells from maGS cells would be of potential value in both clinical and experimental research settings. METHODS AND FINDINGS: Using mouse as a model system, here we show that, similar to sperm, expression of imprinted and paternally expressed miRNAs (miR-296-3p, miR-296-5p, miR-483) were consistently higher (P<0.001), while those of imprinted and maternally expressed miRNA (miR-127, miR-127-5p) were consistently lower (P<0.001) in GS cells than in control embryonic stem (ES) cells. DNA methylation analyses of imprinting control regions (ICR), that control the expression of all imprinted miRNAs in respective gene clusters (Gnas-Nespas DMR, Igf2-H19 ICR and Dlk1-Dio3 IG-DMR), confirmed that imprinted miRNAs were androgenetic in GS cells. On the other hand, DNA methylation of imprinted miRNA genes in maGS cells resembled those of ES cells but the expression pattern of the imprinted miRNAs was intermediate between those of GS and ES cells. The expression of imprinted miRNAs in GS and maGS cells were also altered during their in vitro differentiation and varied both with the differentiation stage and the miRNA. CONCLUSIONS: Our data suggest that GS cells have androgenetic DNA methylation and expression of imprinted miRNAs which changes to ES cell-like pattern upon their conversion to maGS cells. Differential genomic imprinting of imprinted miRNAs may thus, serve as epigenetic miRNA signature or molecular marker to distinguish GS cells from maGS cells.